Predictors of Intestinal Parasites among Food Handlers in Goba Town, Southeast Ethiopia, 2020. (7th June 2022) - Lette, Abate; Negash, Getahun; Kumbi, Musa; Hussen, Abduljewad; Kassim, Jeylan; Zenbaba, Demisu; Gezahgn, Habtamu; Bonsa, Mitiku; Aman, Rameto; Abdulkadir, Adem
Abstract : Background . Globally, around 1.9 million people were dying due to food-borne diseases annually, and intestinal parasites infected one-third of the population, according to estimates and more prevalent in developing countries due to poverty. This study assessed predictors of intestinal parasites among food handlers working in Goba towns. Methods . A laboratory-based cross-sectional study was conducted from October to December 2020. Clean, dry, and leak-proof stool cups were used to collect the samples. The SPSS version 20 computer software was used to enter and clean the data, code it, and analyze it. The researchers performed binary and multivariable logistic regression analyses, with a p value of 0.05 considered significant. Result . A total of 98 (34%) of the 288 food workers tested positive for various intestinal parasites. Giardia lamblia was the most common parasite, with 42 (14.6%), followed by Entamoeba histolytica/dispar with 31 (10.8%), Ascaris lumbricoides with 8 (2.8%), Taenia species with 5 (1.7%), and E. vermicularis with 4 (1.4%). Six (2%) of the 98 positive food handlers had two infections. E. histolytica and G. lamblia were the most common parasites found in mixed infections. Hand washing with soap and water before handling food (AOR: 3.06, 95% CI: 1.16, 7.26) and untrimmed fingernail status (AOR: 2.3, 95% CI: 1.14, 4.34) were found to be strongly linked to intestinal parasite infection. Conclusion . In this investigation, intestinal parasite species were found in 34% of stool samples. Independent predictors of intestinal parasite infection were fingernail status and hand washing with water and soap use before food handling. To control intestinal parasite infection among food handlers in the research area, personal hygiene and ambient cleanliness should be improved.